Current practice variations in the management of anterior cruciate ligament injuries in Delhi - Vaishya, Raju (J Clin Orthop Trauma, 2016)
BACKGROUND: The aim of this study was to determine the current practices and preferences of the arthroscopic surgeons of Delhi in the diagnosis, treatment and rehabilitation of patients with anterior cruciate ligament (ACL) injury. METHODS: It was a cross-sectional descriptive study conducted among arthroscopic surgeons of Delhi. A survey was conducted using a questionnaire that was sent either by e-mail or by direct contact to all sixty arthroscopic surgeons of Delhi. RESULTS: Forty-eight (80%) surgeons responded to our questionnaire. Maximum participants (83.3%) used semitendinosus/gracilis tendon autograft for ACL reconstruction (ACLR) and only 2.1% were using bone-patellar-tendon-bone (BPTB) autograft. Most preferred method of graft fixation was an ‘interference screw’ on the tibial side and an ‘endobutton’ on the femoral side, which was preferred by 95.83% and 93.75% surgeons, respectively. Almost all respondents (97%) used a bio-absorbable interference screw for tibial side graft fixation. Postoperative bracing was advised for <3 weeks by 47.9% surgeons and for 3–6 weeks by 31.3%. The results were analysed using statistical analysis. CONCLUSION: Surgeon preferences in ACLR differ considerably among the arthroscopic surgeons of Delhi. There is majority consensus for using Hamstring autograft (single bundle) with a suspensory fixation on the femoral side and an aperture fixation on the tibial side. Transportal technique of making the femoral tunnel and preservation of amputation stump were the preferred methods. However, differences exist over the timing of surgery, rehab after surgery, pain management, etc.